Development of Simplified Seedling Transplanting Device for Supporting Efficient Production of Vegetable Raw Materials - Luhua Han; Daqian Xiang; Qianqian Xu; Xuewu Du; Guoxin Ma; Hanping Mao (Applied Sciences, 2023)
Efficient greenhouse production has a great supporting role in the development of vegetable agricultural and sideline product processing. In this paper, a simplified automatic transplanting device was designed and evaluated in a laboratory. The device mainly consists of a seedling pick-up gripper, a transplanting manipulator, two conveyors and a control system. The flexible multi-pin gripper was designed to effectively grasp, hold, and release seedlings. Through a combination innovation of the linear modules, the transplanting manipulator was designed to move the seedling gripper to the desired working position. The conveyors were the pallet-type double-row chain transmission system for automatic feeding of plug trays and growth pots. The control system was developed to coordinate each of the aforementioned function units. The multi-factor orthogonal and transplanting performance experiments were carried out under the standard seedling agronomy. The results showed that the transplanting frequency and the pick-up depth significantly affected the transplanting quality. When the transplanting frequency was 15 plants/min, the tightened spring force was 1.2 N, and the pick-up penetration depth was 35 mm, the optimum effects of automatic transplanting seedlings could be achieved. The maximum success in transplanting seedlings was 95.47% for local vegetable crops. The developed prototype could realize less waste of seedling resources at the farm level.